2022
DOI: 10.1002/jssc.202200214
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics profiling of zebrafish liver through untargeted liquid chromatography‐high resolution mass spectrometry

Abstract: Lipidomics analysis of zebrafish tissues has shown promising results to understand disease‐related outcomes of exposure to toxic substances at a molecular level. However, knowledge about their lipidome is limited, as most untargeted studies only identify the lipids that are statistically significant in their setup. In this work, liquid chromatography‐high resolution mass spectrometry was used to study different aspects of the analytical workflow, that is, extraction solvents (methanol/chloroform/water (3/2/2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Lipidomic analysis can also be applied to specific organs from adult zebrafish. For instance, livers from 6-month-old animals were analyzed with different MS techniques, identifying 712 unique lipid species from four categories (fatty acyls, glycerolipids, glycerophospholipids, and sphingolipids) [109]. Moreover, adult zebrafish brains have been analyzed for changes in the lipid profile after exposure to different xenobiotics [102,110].…”
Section: Zebrafish Lipidomicsmentioning
confidence: 99%
“…Lipidomic analysis can also be applied to specific organs from adult zebrafish. For instance, livers from 6-month-old animals were analyzed with different MS techniques, identifying 712 unique lipid species from four categories (fatty acyls, glycerolipids, glycerophospholipids, and sphingolipids) [109]. Moreover, adult zebrafish brains have been analyzed for changes in the lipid profile after exposure to different xenobiotics [102,110].…”
Section: Zebrafish Lipidomicsmentioning
confidence: 99%
“…A recent review of bioinformatics tools for MS-based lipidomics analysis revealed over 30 open-access software tools for lipidomics data processing and annotation 16 . MS-Dial, for instance, is one of the most 6 used software tools due to its versatility and free access, making it widely adopted in the lipidomics field [16][17][18] . Some annotation tools, such as Lipid Annotator, are not freely accessible, limiting their usage compared to other more widely available tools.…”
Section: Comprehensive Workflow For An Accurate Lipid Annotation Usin...mentioning
confidence: 99%
“…Driven by the biological significance of lipids, lipidomics has developed as an emerging omics science. In recent years, MS, especially hyphenated with ultrahigh performance liquid chromatography, enables rapid separation and sensitive detection of hundreds of lipids [18,19].…”
Section: Introductionmentioning
confidence: 99%